# Highest Common Factor of Polynomials by Factorization

How to find the highest common factor of polynomials by factorization?

Let us follow the following examples to know how to find the highest common factor (H.C.F.) or greatest common factor (G.C.F.) of polynomials by factorization.

Solved examples of highest common factor of polynomials by factorization:

1. Find out the H.C.F. of a2b + ab2 and a2c + abc by factorization.

Solution:

First expression = a2b + ab2

= ab(a + b)

= a × b × (a + b)

Second expression = a2c + abc

= ac(a + b)

= a × c × (a + b)

It can be seen, in both the expressions ‘a’ and ‘(a + b)’ are the common factors and there is no other common factor.

Therefore, the required H.C.F. a2b + ab2 and a2c + abc is a(a + b)

2. Find the out the H.C.F. of (a2b + a2c) and (ab + ac)2 by factorization.

Solution:

First expression = a2b + a2c

= a2(b + c)

= a × a × (b + c)

Second expression = (ab + ac)2

= (ab + ac) (ab + ac)

= a(b + c) a(b + c)

= a × a × (b + c) × (b + c)

It can be seen that, in both the expressions ‘a’, ‘a’ and ‘(b + c)’ are the common factors and there is no other common factor.

Therefore, the required H.C.F. is a × a × (b + c) = a2(b + c).

3. Find the out the H.C.F. of c(a + b)2, (a2c2 – b2c2) and a(ac2 + bc2) by factorization.

Solution:

First expression = c(a + b)2

= c × (a + b) × (a + b)

Second expression = (a2c2 - b2c2)

= c2(a2 - b2)

= c2(a + b) (a - b)

= c × c × (a + b) × (a - b)

Third expression = a(ac2 + bc2)

= ac2(a + b)

= a × c × c × (a + b)

It can be seen that, c and (a + b) are the common factors of the expressions.

Therefore, the required H.C.F. of c(a + b)2, (a2c2 – b2c2) and a(ac2 + bc2) is c(a + b)

4. Find out the H.C.F. of 3x2(y + z)2 and 6x(y2 - z2) by factorization.

Solution:

First expression = 3x2(y + z)2

= 3x2 (y + z)(y + z)

= 3 × x × x × (y + z) × (y + z)

Second expression = 6x(y2 - z2)

= 6x(y2 - z2)

= 6x(y + z) (y - z)

= 2 × 3 × x × (y + z) × (y - z)

Therefore, the required H.C.F. is 3 × x × (y + z) = 3x(y + z)

Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

## Recent Articles

1. ### Worksheet on Triangle | Homework on Triangle | Different types|Answers

Jun 21, 24 02:19 AM

In the worksheet on triangle we will solve 12 different types of questions. 1. Take three non - collinear points L, M, N. Join LM, MN and NL. What figure do you get? Name: (a)The side opposite to ∠L…

2. ### Worksheet on Circle |Homework on Circle |Questions on Circle |Problems

Jun 21, 24 01:59 AM

In worksheet on circle we will solve 10 different types of question in circle. 1. The following figure shows a circle with centre O and some line segments drawn in it. Classify the line segments as ra…

3. ### Circle Math | Parts of a Circle | Terms Related to the Circle | Symbol

Jun 21, 24 01:30 AM

In circle math the terms related to the circle are discussed here. A circle is such a closed curve whose every point is equidistant from a fixed point called its centre. The symbol of circle is O. We…

4. ### Circle | Interior and Exterior of a Circle | Radius|Problems on Circle

Jun 21, 24 01:00 AM

A circle is the set of all those point in a plane whose distance from a fixed point remains constant. The fixed point is called the centre of the circle and the constant distance is known